2019
DOI: 10.1021/acs.analchem.9b05200
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Atmospheric Pressure Photoionization Mass Spectrometric Monitoring of Initial Pyrolysis Products of Biomass in Real Time

Abstract: Knowledge on the initial and intermediate pyrolysis products of biomass is essential for the mechanistic investigation of biomass pyrolysis and further optimization of upgrading processes. The conventional method can only detect the final products, which do not resemble the initial or intermediate pyrolysis products. Here, we introduce a direct orifice sampling combined with atmospheric pressure photoionization mass spectrometry (APPI-MS) for in situ online analysis of the evolved volatile initial products fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 32 publications
(45 reference statements)
0
35
0
Order By: Relevance
“…Vacuum ultraviolet (VUV) light, produced by discharge lamps, 8 lasers, 9–11 and tunable synchrotron radiation, 3 is an elegant ionization source for mass spectrometry. As a soft ionization process, VUV photoionization can facilitate selective identifications of species to avoid interference from fragmentation 12–15 . The photoionization cross‐section (PICS) is thus the key parameter to quantify the concentration of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum ultraviolet (VUV) light, produced by discharge lamps, 8 lasers, 9–11 and tunable synchrotron radiation, 3 is an elegant ionization source for mass spectrometry. As a soft ionization process, VUV photoionization can facilitate selective identifications of species to avoid interference from fragmentation 12–15 . The photoionization cross‐section (PICS) is thus the key parameter to quantify the concentration of organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Kauppila et al (2016) investigated the nucleophilic aromatic substitution between halogenated benzene dopants and nucleophiles. Zhou et al reported real-time APPI-MS monitoring of initial pyrolysis products of biomass, which revealed the mechanism of biomass pyrolysis (Chen et al, 2020).…”
Section: Apcimentioning
confidence: 99%
“…TG/MS experiments [28, 29] indicate that the formation of phenolic pool is favorable at moderate temperatures (Figures S2 and S3). The phenolic pool‐related oligomers during catalytic pyrolysis of GGGE over HZSM‐5 were probed in gas phase by in situ atmospheric pressure photoionization high‐resolution mass spectrometer (APPI HRMS) combined with a fixed‐bed reactor under isothermal mode [30] . Low volatility of phenolic pool‐related oligomers lead to low concentrations in gas phase while the high oxygen content makes them thermally labile, resulting in a high propensity to lose during the sampling process with traditional technologies.…”
Section: Figurementioning
confidence: 99%
“…The phenolic pool-related oligomers during catalytic pyrolysis of GGGE over HZSM-5 were probed in gas phase by in situ atmospheric pressure photoionization high-resolution mass spectrometer (APPI HRMS) combined with a fixed-bed reactor under isothermal mode. [30] Low volatility of phenolic pool-related oligomers lead to low concentrations in gas phase while the high oxygen content makes them thermally labile, resulting in a high propensity to lose during the sampling process with traditional technologies. The in situ APPI HRMS method used in current work (inserted sketch in Figure 1 a) proceeds without any sample collection and pre-treatment, and the combination of "direct orifice sampling" and in situ APPI method avoids condensation during sampling process and secondary reactions, ensuring the effective detection of reactive intermediates.…”
mentioning
confidence: 99%
See 1 more Smart Citation